Regularização fundiária do território Kalunga ante o processo discriminatório das terras de Cavalcante/GO - Kuramoto, Teruo Rosa (2025)
This dissertation analyzes the process of (non)regularization of land tenure in the Kalunga Quilombo Territory (TQK). The research problem focuses on the failure to guarantee the territorial rights of the Kalunga people, supported by Article 68 of the Transitional Constitutional Provisions (ADCT/CF), as well as other national and international provisions. The safeguarding of territories for traditional communities constitutes a fundamental right, as these communities do not exist without their territories—a fact that underscores the relevance and justification for this study. Our research hypothesis is that part of the private properties established in the TQK, through discriminatory land actions, was irregularly consolidated. Methodologically, a predominantly qualitative approach will be adopted, using the hypotheticodeductive method to analyze the formation of real estate properties in the Kalunga territory through documentary analysis, with the primary source being the judicial discriminatory process of the lands in Cavalcante/GO and maps of the region. The historical method of investigation and a literature review will also be employed. The specific objectives were: 1) To investigate the origins of the Kalunga quilombo and the constitution of its territory; 2) To discuss the formation of private land ownership in Brazil; and 3) To analyze the discriminatory process of the lands in Cavalcante (GO) and the actions (or inaction) of the State of Goiás, the Federal Government, and INCRA regarding the (non)titling of the TQK. The results indicate that Article 150 of the 1947 Constitution of the State of Goiás was responsible for designating the region's unallocated lands. Evidence of irregularities was identified in some properties excluded from the discriminatory action in Cavalcante, as well as negligence by the competent authorities regarding the obligations set forth in Article 68 of the ADCT, given that only 8.58% of the TQK has been definitively titled.